From BaCl2 to Ba(NO3)Cl: significantly enhanced birefringence derived from π-conjugated [NO3]. (2nd September 2021) - Chen, Zhen; Zeng, Hao; Han, Shujuan; Yang, Zhihua; Pan, Shilie
Abstract : The chlorine barium nitrate Ba(NO3 )Cl was synthesized for the first time to the best of our knowledge and found to exhibit a strong birefringence of 0.178 @ 1064 nm, about 19 times that of BaCl2 . Abstract : The chlorine barium nitrate Ba(NO3 )Cl was synthesized, for the first time to the best of our knowledge, by using a mild hydrothermal method. Its structure was observed to feature an ABW-type topology (BaCl-ABW) framework, which can be considered as stacks of honeycomb-shaped sheets. Also, Ba(NO3 )Cl crystals with dimensions of up to 2 × 1 × 0.5 mm 3 were grown. Remarkably, Ba(NO3 )Cl was found to exhibit a short UV cutoff edge (below 213 nm) and a markedly enhanced birefringence (Δ n = 0.178 @ 1064 nm), about 19 times that of its parent phase BaCl2 (Δ n = 0.009 @ 1064 nm). Theoretical calculations indicated that the birefringence enhancement mainly derived from the planar [NO3 ] triangles.